PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TINGKAT PROFITABILITAS, BESARAN PAJAK PENGHASILAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2019 - Napitu, Hoddy Angelina Saragi; Lumbangaol, Romasi (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to determine the effect of implementing Corporate Social Responsibility on profitability (ROA), the amount of income tax in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population of this study are all food and beverage sub manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2019. The sample in this study was obtained by purposive sampling. With a sample of 37 companies with a period of 2 years so that the total number is 74. Data collection techniques use documentation techniques. The analytical method used is a simple linear regression equation using SPSS 22. From the results of the SPSS test, it is known that the t-count value of the CSR variable on ROA is greater than the t-table (t-count > t-table) which is 2.941 > 1.68709 and the value is significantly smaller than the alpha coefficient 0.004 < 0.05. Then the Corporate Social Responsibility variable has a positive and significant effect on the level of profitability. Meanwhile, the t-count value of the CSR variable on PPH is smaller than the t-table (t-count < t-table) which is -1.087 <1.68709 and the significant value is greater than the alpha coefficient 0.281 > 0.05. So the Income Tax Amount has a positive and insignificant effect on the level of Income Tax Amount in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2019 period.